Implementation of Marriage Law and Impacts on The Marriage of Sea Tribal Children in Lipan Island (Pandecta Research Law Journal, 2022)
Child marriage is a case that still occurs in Indonesia, including in the marine tribal community on Lipan Island, Lingga Regency. However, Indonesia already has a set of regulations governing marriage and child protection. This study aims to, first, examine the application of Indonesian regulations regarding marriage to children of the sea tribe. Second, to elaborate on the impacts that occur as a result of the practice of child marriage of sea tribesmen. The method used is empirical legal research. Sources of data come from primary data and secondary data. There are two (2) legal theories used to analyze the research problem, namely the Theory of Legal Effectiveness by Soerjono Soekanto and Theory of Legal Protection by Muchsin. The results of the study indicate that the application of regulations regarding marriage has not been effective when measured by the theory of legal effectiveness and is not in accordance with the meaning of legal protection proposed by Muchsin. There are several impacts resulting from child marriage, namely the non-fulfillment of children’s rights in the fields of health and education. Therefore, it is necessary to make changes to the regulations regarding marriage regarding the opportunity to carry out child marriages with parental permission, in addition to improving the quality of education for the Sea Tribe community on Lipan Island.